(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
This paper proposes a direct torque control with dc voltages balancing strategy for a five-phase induction machine fed by a five-phase three-level diode-clamped inverter. The goal of the proposed multilevel direct toque control is not only to control the machine flux and torque but also to maintain the dc-bus voltage at the required level. This objective can be achieved by using a three-level direct torque control endowed with a balancing strategy based on the effective use of redundant switching states of the inverter voltage vectors. To make this clear, a set of simulation results is presented and discussed to verify the feasibility and effectiveness of the proposed control scheme.